Length-dependent thermopower determination of amine-terminated oligophenyl single molecular junctions formed with Ag electrodes - Kim, Deokhyun; Yoo, Pil Sun; Kim, Taekyeong (Journal of the Korean Physical Society, 2015)
We determine the thermopower of amine-terminated oligophenyl by trapping them between two Ag-electrodes with a temperature difference, using a scanning tunneling microscope-based breaking-junction technique. We find that the Seebeck coefficient (S) is positive for amine-Ag linked highest occupied molecular orbital (HOMO)-conducting junctions. Furthermore, we observe that S increases linearly with the number of phenyls N for Ag as well as Au, which means that the thermopower depends on the molecular length. For these molecules that conduct through the HOMO, junctions formed with Ag electrodes show lower S than those formed with Au electrodes, consistent with the predictable trends based on the alignment of the HOMO with the lower work function of Ag compared to Au. Our work should open a new pathway for designing thermoelectric devices with versatile materials based on organic molecules.